Development of Context-Based Interactive PowerPoint Materials to Improve Early Childhood Numeracy Skills - Rismauli Malau; I Made Tegeh; Dewa Gede Firstia Wirabrata (Universitas Pendidikan Ganesha, 2026)
Early childhood numeracy learning often faces challenges due to the use of conventional and less interactive teaching methods, which result in low motivation and engagement among children during the learning process. This study aims to develop and evaluate the feasibility of an interactive PowerPoint learning media based on a contextual approach to improve the quality of numeracy learning for children aged 5–6 years. The study employed a Research and Development (R&D) method using the ADDIE model, limited to the Analysis, Design, and Development stages. The research subjects consisted of one material expert, one media expert, and four early childhood education teachers as practitioners. Data were collected through interviews, literature studies, and questionnaires using a Likert scale. The research instruments included expert validation sheets and practitioner readability test sheets. Data were analyzed using descriptive quantitative analysis techniques to determine the validity and feasibility of the developed media. The results showed that the developed media obtained an average score of 3.90 from the material expert and 3.85 from the media expert, both categorized as highly valid, while the readability test conducted by practitioners obtained an average score of 3.43, categorized as good. These findings indicate that the contextual-based interactive PowerPoint media is feasible to be used as an alternative numeracy learning medium that is more engaging, interactive, and meaningful for early childhood learners.